2008
DOI: 10.1203/pdr.0b013e31815f00f9
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding Reduces Endothelial Nitric Oxide Synthase in the Caudal Intestinal Microvasculature of Preterm Piglets

Abstract: ABSTRACT:The initiation of enteral feeding represents a challenge to the neonatal intestinal microcirculation, especially in preterms where it predisposes to necrotizing enterocolitis (NEC). We hypothesized that a structural microvascular deficiency may occur when enteral feeding is initiated in preterm piglets susceptible to NEC. Stereologic volume densities of a pan-endothelial marker (vWF), and the main vasodilator endothelial nitric oxide synthase (eNOS), were determined along the small intestine of 1) unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…There is evidence indicating that NO suppresses IL-18 processing by inhibiting caspase-1 activity (16). In this study we showed that endothelial NOS (eNOS) mRNA was downregulated as an early response to formula feeding, consistent with the earlier indication that low mucosal eNOS was related to NEC lesions in preterm pigs (32). Likely an early feeding-and ischemiainduced decrease in NO levels results in activation of caspase-1 and further secretion of IL-18.…”
Section: Discussionsupporting
confidence: 91%
“…There is evidence indicating that NO suppresses IL-18 processing by inhibiting caspase-1 activity (16). In this study we showed that endothelial NOS (eNOS) mRNA was downregulated as an early response to formula feeding, consistent with the earlier indication that low mucosal eNOS was related to NEC lesions in preterm pigs (32). Likely an early feeding-and ischemiainduced decrease in NO levels results in activation of caspase-1 and further secretion of IL-18.…”
Section: Discussionsupporting
confidence: 91%
“…Animal studies also have shown that iNOS is upregulated in a neonatal rat NEC model 57 and that iNOS mediates LPS-induced increase in intestinal permeability 111 . In the intestine of neonatal rats fed with formula eNOS and nNOS were downregulated while iNOS was upregulated when compared with dam fed controls 112 and in piglets, formula feeding downregulated eNOS 113 . When L-NAME, a NO synthase inhibitor, was administered intravenously in a neonatal piglet model of NEC, it worsened the intestinal injury while L-arginine, a NO synthase substrate, attenuates intestinal injury 114 .…”
Section: Nitric Oxide (No)mentioning
confidence: 89%
“…In these baseline studies, NEC is produced in vivo; and serum levels or tissue levels of various mediators are then determined after killing of the animal or removal of the operative specimen [16][17][18][19][20][21][22][23]. Alternately, groups have explored microvascular responses in NEC with different vasoactive mediators by explanting intestinal blood vessels and evaluating their activity ex vivo under a variety of conditions [24].…”
Section: Discussionmentioning
confidence: 99%